Adhesion properties of a three-layer system based on RF-magnetron sputter deposited calcium-phosphate coating and silver nanoparticles - Tkachev M. S.; Melnikov E. S. Evgenii Sergeevich; Surmeneva M. A. Maria Alexandrovna; Sharonova A. A. Anna Aleksandrovna; Surmenev R. A. Roman Anatolievich; Korneva O. S. Olga Sergeevna; Shulepov I. A. Ivan Anisimovich; Loza K.; Epple M. (New materials and nanotechnologies, 2016)
Title screen